What are the Effects of Financial Inclusion to the Business Environment in Azerbaijan? - Alkaramov, Tusi (ADA University, 2020)
This work is aimed to study the effects of financial inclusion on business environment in Azerbaijan. The paper will include review of literature that covers main issues regarding the topic and will try to figure out international practice that is used currently. The literature will cover relation between current financial accessibility of population and businesses in Azerbaijan and what measures are taken in this sphere globally. Afterwards, there will be discussed which research methodology was used and what possible contributions can this research make to the current issue. Furthermore, there will be made analysis of findings which will give broader idea about topic. Finally, there will be made discussion and analysis of all covered data and come up with specific conclusions about the work done. At the end there will be discussed the limitations of research that was faced and what are the effects of these limits for the research.
Keywords: Business; Azerbaijan -- Economic conditions.; Azerbaijan -- Economic policy.; Azerbaijan -- Management Structure.